College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 1 - Review Exercises: 15



Work Step by Step

We solve: $\sqrt{2x-3}+x=3$ $\sqrt{2x-3}=3-x$ $2x-3=(3-x)^2$ $2x-3=9-6x+x^{2}$ $-3-9=x^2-6x-2x$ $x^{2}-8x+12=0$ $(x-2)(x-6)=0$ $(x-2)=0$ or $(x-6)=0$ $x=2$ or $x=6$ However, the solution $x=6$ does not work in the original equation, so we throw this solution out: $\sqrt{2*6-3}+6=\sqrt{12-3}+6=\sqrt{9}+6=3+6=9\neq 3$ Thus the only solution is $x=2$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.